Implementasi Sosial Media Marketing Pada UMKM Bata Press UD Intan Desa Pejaten Kabupaten Tabanan - Ni Luh Laksmi Rahmantari; Made Putri Ariasih; Ni Komang Mela Tri Utari (CV. Multi Kreasi Media, 2022)
Pejaten Village is one of the villages in Kediri District, Tabanan Regency, Bali Province which is famous in the clay craft sector. One of the industrial products is press brick. From the results of the research conducted, press brick products should be more widely known outside the island of Bali to foreign countries, but because the marketing techniques used are still conventional, namely word of mouth marketing, making brick press products less well known to the wider community. Based on this potential, the researchers implemented training and mentoring strategies for MSMEs in Pejaten Village, namely at UD. Diamond. The purpose of training and mentoring for SMEs in Pejaten Village is to introduce the press brick industry more broadly. From the results of this study, a solution emerged in the form of an invitation to press brick craftsmen to find out more about the right marketing techniques using social media.